Development and validation of a manual using the Rood's approach for children with cerebral palsy - Lintag, Jeanzen Michelle B. (2008)
This study is an attempt to develop and validate a manual on Rood's Approach in a classroom setting for children with cerebral palsy (CP) for use of the transdisciplinary team. It followed a single-subject experimental design that was replicated to 5 children with CP who have similar characteristics. Two instruments were used by 6 validators and 3 assessors, namely, the Rood's Approach Manual Evaluation Sheet (RAMES) and the Classroom Activity Performance Assessment (CAPA) Form. Based on the experts' judgment, the manual was found to be valid for use. Based on experimentation, the performances of students with CP during classroom activities showed significant improvements upon employment of Rood's Approach strategies.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Cerebral palsied children -- Education -- Philippines -- Manila Metropolitan Area; Special education -- Philippines -- Manila Metropolitan Area